Differential impacts of land use regimes on soil aggregate stability and aggregate-associated organic carbon sequestration in semi-arid Vertisols - Ponyane, Patience; Dina Ebouel, Ferdinand J.; Eze, Peter N. (Frontiers in Soil Science, 2025)
Land use impacts on soil aggregate stability and carbon sequestration, which are critical biogeochemical indicators of soil health, are largely understudied in semi-arid Vertisols. This study aims to bridge the gap. Here, the impacts of different land use regimes (arable land, grassland exclosures, natural exclosures, and pastures) on aggregate stability and soil organic carbon contents were investigated in the semi-arid Vertisols of the Pandamatenga Plains – an important regional agricultural hotspot in Botswana. Soil samples were collected at three depths (0-15, 15-30, and 30–45 cm) and fractionated into macroaggregates (> 0.25 mm) and microaggregates (< 0.25 mm) using the wet sieving method. Soil aggregate stability was assessed using indices including water-stable aggregates (WSA), mean weight diameter (MWD), geometric mean diameter (GMD), and the content of > 0.25 mm aggregates (R0.25). Routine laboratory procedures were used to analyze the pH, Electrical conductivity, calcium carbonate, exchangeable cations, soil organic carbon, bulk density, particle size distribution, and clay mineralogy. Findings indicate that land use had a substantial impact on soil structural stability and soil organic carbon dynamics. Natural exclosures recorded the highest MWD (2.95 mm) and GMD (1.5 mm), reflecting a well-developed soil structure. Grassland exclosures and pastures showed intermediate stability, while arable land had the lowest aggregate stability (MWD = 0.5 mm), reflecting degradation. Water-stable aggregates (WSA) varied with land use types and aggregate sizes, with arable land having higher WSA (71.91%) in smaller fractions, which are more prone to erosion and natural exclosures higher WSA (72.07%) in larger sizes, supporting greater cohesion. Pastures had the most meso aggregates. R0.25 exhibited uniformity across various land use types due to high clay contents. Soil organic carbon stocks were highest in natural exclosures (250 kg C m-2) and lowest in pastures (80 kg C m-2), with macroaggregates (>0.25 mm) contributing most significantly to carbon storage, underscoring their role in carbon storage. A positive correlation (r = 0.7) was observed between MWD and aggregate-associated carbon. These findings highlight the importance of long-term exclosures that minimize disturbance and promote vegetation cover to improve soil structure and carbon storage.